2015
DOI: 10.4238/2015.september.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting circulating tumor cells in patients with advanced non-small cell lung cancer

Abstract: ABSTRACT. We explored the expression and clinical significance of circulating tumor cells (CTCs) in patients with advanced non-small cell lung cancer (NSCLC). Sixty-six patients with advanced NSCLC at the Oncology Department of Jinzhou Hospital were selected as an observation group between February and December 2013. Healthy volunteers and 20 benign lung disease patients were taken as a control group. Peripheral blood CTCs in the observation and control groups were detected using the CellSearch ® . CTC detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
1
13
1
Order By: Relevance
“…The correlation with survival of CTC counts was not reported by Xu and collaborators, who identified peripheral blood CTCs in 47/66 (71.2%) chemo-naïve stage IV NSCLC patients by using the CellSearch (35). However, they found that the number of patients with ≥3 CTCs decreased significantly after two cycles of chemotherapy.…”
Section: Prognostic and Predictive Value Of Ctc In Advanced Nsclcmentioning
confidence: 62%
See 1 more Smart Citation
“…The correlation with survival of CTC counts was not reported by Xu and collaborators, who identified peripheral blood CTCs in 47/66 (71.2%) chemo-naïve stage IV NSCLC patients by using the CellSearch (35). However, they found that the number of patients with ≥3 CTCs decreased significantly after two cycles of chemotherapy.…”
Section: Prognostic and Predictive Value Of Ctc In Advanced Nsclcmentioning
confidence: 62%
“…However, they found that the number of patients with ≥3 CTCs decreased significantly after two cycles of chemotherapy. In this respect, a count ≥3 CTCs after two cycles was associated with an higher rate of progressive disease (P<0.05) (35).…”
Section: Prognostic and Predictive Value Of Ctc In Advanced Nsclcmentioning
confidence: 99%
“…To date, "CellSearch System" is the only Food and Drug Administration (FDA)-approved technique used to detect CTCs, which uses epithelial markers like EpCAM and CKs. 3,[10][11][12][13][14]23 Epithelial cells undergo EMT to increase the capacity of invasiveness and metastasis, resulting in loss of expression of epithelial cell markers such as EpCAM and/or CKs, and thus, EpCAM-based techniques may not efficiently capture CTCs with mesenchymal characteristic following EMT. Mani et al 26 revealed that cells acquire stem-cell-like properties during EMT by up-regulation of CD44 and down-regulation of CD24 as well as increased expression of other stem cell phenotypic markers.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Till date, epithelial cell surface markers are being used as a sole modality for isolation of rare population of CTCs by various systems. [10][11][12][13][14] Utilizing these markers for the effective isolation of CTCs may provide erroneous results as they result in the down-regulation of epithelial cell markers during the epithelial-mesenchymal transition (EMT). Increasing evidences suggest that an apparently small subset of CTCs also bears CSC characteristics based on their ability to give rise to tumors and thus could be considered circulating tumor stem cells (CTSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Six studies assessed the role of CTCs in chemo-naïve NSCLC patients that received standard treatment with chemotherapy [48][49][50][51][52][53] (Table 3). Krebs stage III.…”
Section: Prognostic Value Of Ctcs In Advanced/metastatic Nsclcmentioning
confidence: 99%